IDENTIFIKASI ZONA BAHAYA GEMPA BUMI BERDASARKAN PERCEPATAN TANAH MAKSIMUM DI KOTA SEMARANG - Koesuma, Sorja; Fajrin, Viola; Sunardi, Bambang (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2022)
Semarang City as the Capital of Central Java Province requires an earthquake-prone map. It is required since there are two active faults in Semarang, namely the Semarang fault (part of the Baribis - Kendeng fault) and the Ungaran fault. Moreover, Semarang City is composed of alluvial layers that can accelerate earthquake waves. This study aims to determine site class, peak ground acceleration (PGA) in bedrock, PGA at ground level and earthquake hazard index in Semarang City. In this study, the calculation of peak ground acceleration uses the method in SNI 1726: 2019, while the earthquake hazard index refers to the JICA classification. As input data in the form of the peak ground acceleration value in bedrock, the average shear wave velocity to a depth of 30 meters (Vs30) to determine the site class, as well as the value of the amplification factor. The calculation results in almost all areas of Semarang City have a high earthquake hazard index and only Genuk sub-district has a moderate hazard index. The main determinants of peak ground acceleration at the surface are the source of the earthquake and the rock type